Meningkatkan Hasil Belajar Pada Materi Struktur dan Keseimbangan Pasar Dengan LKPD Berbasis Teams Games Tournament (TGT) - Wulandari, Oktavia Rukmana (Universitas Pendidikan Ganesha, 2020)
Teaching material is a supporting factor for students in the learning process. However, the irrelevance of teaching materials used will result in not achieving learning objectives. The purpose of this research is to describe the feasibility of LKPD with the Team Games Tournament model, to analyze the practicality and effectiveness of using LKPD with the TGT model. The research method used is Research & Development using the 4D model from Thiagarajan. The research procedure consisted of 4 phases, define, design, develop, and disseminate. Instruments of product validity were obtained from material experts, graphic experts, evaluation experts and students' post-test results. The results of this study indicate that (1) The development of TGT-based LKPD is considered Eligible, based on the average validation of experts at 77.92%. (2) LKPD is considered effective in learning in terms of learning outcomes as well as the students' skills in working on HOTS questions increased with the final result 82.14% so that students are declared to have passed completeness. (3) LKPD is considered practical in learning because the development carried out is able to increase the interest and relaxation of students in the learning process according to the results of research students' responses where an interest in the product as much as 80.60% is said to be feasible. Based on these results it can be said that TGT based LKPD is declared to be very feasible and good for use in the learning process because it shows an increase in learning outcomes after using this LKPD.